Experimental study of a symmetric air-cushion-based floating solar platform: hydrodynamic performance and power output - Mi, Chenhao; Lyu, Xiangcheng; Ou, Binjian; Wong, Anson; Verdin, Patrick G.; Huang, Luofeng (MDPI, 2026)
Solar energy is one of the fastest-growing contributors to the global energy market. Floating photovoltaic (FPV) systems have emerged as a promising solution to the land-use challenges faced by conventional solar farms. However, the extension of FPV systems to offshore environments is hindered by dynamic wave–structure interactions. Inspired by air-cushion vessels, this study proposes and experimentally validates a novel FPV platform supported by an inflatable air cushion that provides adjustable stiffness and passive damping through air compressibility and wave-induced volumetric deformation. The investigated platform adopts a symmetric structural configuration, which inherently mitigates asymmetric roll and yaw coupling to maintain a balanced hydrodynamic response and stable power generation under wave action. Wave tank experiments were conducted to evaluate the coupled hydro-elastic response, mooring loads, and power generation stability under varying wave heights. The results show that the air-cushion design can significantly reduce peak mooring loads by over 50% compared with the catamaran benchmark. The highest pressure of 20 mbar increases structural stiffness but causes wave-induced losses of up to 30%. Conversely, the lowest pressure of 5 mbar results in excessive compliance that amplifies pitch and heave motion. A moderate pressure of 10 mbar acts as the optimal damping condition within the tested pressure range, suppressing motion resonance while maintaining power output stability. These findings demonstrate the potential of air-cushion integration for offshore FPV adaptability.
This article belongs to the Special Issue Advances in Fluid Dynamics and Energy Systems: Applications of Symmetry and Asymmetry
Keywords: floating photovoltaic; air cushion; symmetry; wave tank experiments; hydrodynamic response; hydro-optical coupling; power output